Match-play movement demands of international and domestic women`s rugby sevens players in an elite dual-level tournament - Brosnan, R. J.; Visentin, D.; Watson, G.; Twentyman, C.; Stuart, W.; Schmidt, M. (Science and Medicine in Football, 2024)
Objectives: To characterize and compare match-play movement demands via Global Positioning Systems (GPS) between international and domestic women`s rugby sevens players performing in a novel elite dual-level tournament, with consideration to position and tournament characteristics. Design: Fifty-four rugby sevens players; twenty-one international(5 speed edges, 8 backs, 8 forwards), and thirty-three domestic(10 speed edges, 11 backs, 12 forwards) wore GPS devices during an elite dual-level tournament covering 2 seasons, with 367 full match-play data files analysed. Internationaland domestic players were distributed evenly between competing teams. Methods: Match-play movement demands were characterized by distance, speed, and acceleration-based indices from 5 to 10 Hz GPS devices. Results: International players recorded significantly higher high-intensity match-play movement demands compared to domestic players in distance in high and very high-speed zones (P = 0.01, P = 0.03, P = 0.01, P = 0.03), maximal acceleration (P = 0.001), maximal velocity (P < .001), speed exertion (P = 0.01), , and acceleration load density (P = 0.03) . Positional analysis demonstrated forwards displayed the largest significant differences between international and domestic players. . Total and relative match-play movement demands of the dual-leveltournament also showed comparable demands to previous international tournament research . Conclusions: Results identify key points of difference in match-play movement demands between player levels in women`s rugby sevens, and provides important information on the characteristics of playing positions, and of a dual-level tournament of this nature. This will improve the design and implementation of structures from domestic to international level.